Digital Footprints As Personal Archives: Analysis Of Awareness In Managing Digital Footprints As Personal Archives Among Vocational Students Of Universitas Indonesia - Nawal Aulia; Medyana Bilqiis; Ghea Syafa Maura; Chelsea Devina Putri; Hafizal Hasburrahman; Sabrina Tsana Wigati (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The rapid advancement of technology in the era of Society 5.0 has transformed various aspects of human life, integrating digital systems into daily activities and communication. This transformation resulted in a massive dissemination of personal information online in the digital sphere, forming what is recognized as digital footprints. However, despite the conveniences of digitalization, individuals might face significant risks of data misuse by unauthorized parties due to how vast the digital system is. This case might occur if one lacks awareness and conducts inadequate management of personal data. National surveys in Indonesia by CfDS UGM revealed that while most internet users claim to understand personal data, only few can accurately identify and manage it effectively. This study aims to analyze the level of awareness and understanding of digital footprint management as personal archives among the academic community of Vocational Education, Universitas Indonesia using a mixed-methods approach. Grounded in José Van Dijck’s (2007) mediated memory theory, this study conceptualizes digital footprints as personal archives that represent individual memory in the digital sphere. This research seeks to highlight the importance of archival science beyond institutional contexts and promoting its application to individuals. This article is expected to provide theoretical insights within archival science and digital information studies, and also as practical strategies to enhance digital literacy and personal data protection.